OPTIMIZATION OF FIBER REINFORCED CONCRETE IN DRAINAGE COVER APPLICATIONS - KALDOKE, N.M.; KULKARNI, S.K KULKARNI (Innovative Research Thoughts, 2018)
Many a times the drainage covers that cover potholes for sewage and other underground civil access points are made from cast concrete. These structures lack durability owing to non- flexibilty and do not sustain under cyclic load as in the vehicles on road moving over this drainage cover point . Considering that there are two load cycles per vehicle passing the durability study needs to be done for the structure. More over innovation needs to be done in this regards as to changes in material used for these drainage covers, FRC being a good option . This project will study the application of FRC technology to the drainage cover manufacturing , more over effect of specific gravity of mixture before it is cast ( in form of slump test) on the structural durability and integrity of the product. The FRC will be developed, cast and tested in form of slabs that will be tested on the set up developed. Curing time will be same for all specimens as to 28 days. The durability of the specimens will be determined as to number of cycles the specimen with stands before failure, process variabiles being the specific gravity of mixture to be cast (tested by slump test ) and percentage of fiber additive.